Lattice Boltzmann Methods for Multiphase Flow Simulations across Scales (Communications in Computational Physics, 2018)
The simulation of multiphase flows is an outstanding challenge, due to theinherent complexity of the underlying physical phenomena and to the fact that multiphaseflows are very diverse in nature, and so are the laws governing their dynamics.In the last two decades, a new class of mesoscopic methods, based on minimal latticeformulation of Boltzmann kinetic equation, has gained significant interest as anefficient alternative to continuum methods based on the discretization of the NS equationsfor non ideal fluids. In this paper, three different multiphase models based onthe lattice Boltzmann method (LBM) are discussed, in order to assess the capability ofthe method to deal with multiphase flows on a wide spectrum of operating conditionsand multiphase phenomena. In particular, the range of application of each methodis highlighted and its effectiveness is qualitatively assessed through comparison withnumerical and experimental literature data.